2006
DOI: 10.1029/2005gc000962
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of weathering patterns in the Indo‐Burman Ranges over the last 280 kyr: Effects of sediment provenance on 87Sr/86Sr ratios tracer

Abstract: [1] A high-resolution study of mineralogy and major element geochemistry combined with Sr and Nd isotopes has been conducted on high sedimentation rate cores collected off the Irrawaddy River mouth in the Andaman Sea and the Bay of Bengal to reconstruct the erosional and weathering history of the Irrawaddy River basin. In both cores, eNd(0) values imply that both glacial and interglacial sediments share a common crustal source: the Irrawaddy River. Strong glacial/interglacial cycles are recorded by 87 Sr/ 86 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(134 citation statements)
references
References 44 publications
9
117
1
1
Order By: Relevance
“…K is more abundant in feldspar and illite so that the variations in the K/Al ratio may reflect the variations in feldspar and illite abundances present in the sediments due to inherent source signature or due to weathering and transport. Higher K concentration shows more feldspar and illite (Colin et al, 1999;Singh et al, 2008) (Goldstein and O'Nions, 1981;Bouquillon et al, 1990;France-Lanord et al, 1993;Galy et al, 1996Galy et al, , 2010Winter et al, 1997;Pierson-Wickmann et al, 2001;Clift et al, 2002;Singh and France-Lanord, 2002;Banner, 2004;Ahmad et al, 2005Ahmad et al, , 2009Colin et al, 2006;Singh et al, 2008;Viers et al, 2008;Rahaman et al, 2011;Tripathy et al, 2011;Goswami et al, 2012;Awasthi et al, 2014;Ali et al, 2015). These isotope pairs are used as reliable proxies to track the sediment sources, as there are distinct differences in their composition in the different lithologies supplying these sediments.…”
Section: Discussion Major Element Compositions and Implications For Pmentioning
confidence: 99%
“…K is more abundant in feldspar and illite so that the variations in the K/Al ratio may reflect the variations in feldspar and illite abundances present in the sediments due to inherent source signature or due to weathering and transport. Higher K concentration shows more feldspar and illite (Colin et al, 1999;Singh et al, 2008) (Goldstein and O'Nions, 1981;Bouquillon et al, 1990;France-Lanord et al, 1993;Galy et al, 1996Galy et al, , 2010Winter et al, 1997;Pierson-Wickmann et al, 2001;Clift et al, 2002;Singh and France-Lanord, 2002;Banner, 2004;Ahmad et al, 2005Ahmad et al, , 2009Colin et al, 2006;Singh et al, 2008;Viers et al, 2008;Rahaman et al, 2011;Tripathy et al, 2011;Goswami et al, 2012;Awasthi et al, 2014;Ali et al, 2015). These isotope pairs are used as reliable proxies to track the sediment sources, as there are distinct differences in their composition in the different lithologies supplying these sediments.…”
Section: Discussion Major Element Compositions and Implications For Pmentioning
confidence: 99%
“…The Andaman Sea drilling sites are within the Nicobar-Andaman Basin, bounded on either side by the Diligent and Eastern Margin Faults. Terrigenous sediment supply to the Andaman Sea is dominantly from the Irrawaddy and Salween Rivers (Colin et al, 1999(Colin et al, , 2006. Analysis of Andaman Sea surface sediments indicates that foraminifers are abundant and well preserved shallower than ~1800 mbsl (>100,000 individuals/gram) and decrease to <100 individuals/gram deeper than 3000 mbsl (Frerichs, 1971).…”
Section: Geological Settingmentioning
confidence: 99%
“…We also compared Sr and Nd isotopic composition of the Firozpur core sediments with the existing records generated from the Bay of Bengal (France-Lanord et al, 1993;Galy et al, 2008Galy et al, , 2010Colin et al, 1999Colin et al, , 2006 and the Ganga Plain sediments (Rahaman et al, 2009;Agrawal et al, 2013a). France-Lanord et al (1993) investigated variations in the Sr and Nd isotopic ratios in a sediment core from the Bay of Bengal spanning 17 Ma time period and showed that the dominant source of these sediments is the Higher Himalayan Crystallines with lesser contribution from the LH.…”
Section: Comparison With Existing Sr Isotopic Records Of Global Rivermentioning
confidence: 99%
“…It confirms the stable erosion regime of the Himalaya during millennium and millennial time scale. Colin et al (1999Colin et al ( , 2006 used Sr and Nd isotope composition of sediment core collected from the Bay of Bengal and the Andaman Sea to identify the sources of sediments. On the basis of Sr and Nd isotope Coiln et al (1999Coiln et al ( , 2006 suggested that these basins receive sediments from multiple sources.…”
Section: Comparison With Existing Sr Isotopic Records Of Global Rivermentioning
confidence: 99%